A distributed QoS mechanism for ad hoc network. (1st October 2012) - Abbas, Cláudia Jacy Barenco; Villalba, Luis Javier García; Orozco, Ana Lucila Sandoval
This paper presents a new mechanism of QoS Medium Access in ad hoc IEEE 802.11 network. The Distributed Coordination Function Ad Hoc (DCFAH) offers a fair medium access mechanism and a minimum bandwidth to all stations that ask for Quality of Service (QoS). Also is concerned about the delay and jitter metrics. The DCFAH uses the Enhanced Distributed Channel Access (EDCA) mechanism to provide the difference of QoS services among flows inside a station. The fairness of DCFAH is provided with the use of a distributed control mechanism during the QoS period. The DCFAH also provides the Best Effort (BE) service to applications that do not need QoS.